2006
DOI: 10.1097/01.cad.0000217420.14090.a9
|View full text |Cite
|
Sign up to set email alerts
|

A case of glassy cell carcinoma of the uterine cervix that responded to neoadjuvant chemotherapy with paclitaxel and carboplatin

Abstract: Glassy cell carcinoma of the uterine cervix is a rare tumor, and has a poor prognosis because of its aggressive clinical behavior and resistance to radiotherapy and chemotherapy. We report a case of bulky glassy cell carcinoma of the uterine cervix that effectively responded to paclitaxel and carboplatin in a neoadjuvant setting. The patient was a 30-year-old woman who became aware of vaginal bleeding and was referred to our hospital because of a cancerous tumor of the uterine cervix. Physical examination show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…The other two women with adjuvant PC chemotherapy are alive in disease‐free state in for more than 4.5 years. Some reports showed that PC chemotherapy is effective for primary and recurrent GCC of the cervix 8–11 . Nasu et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other two women with adjuvant PC chemotherapy are alive in disease‐free state in for more than 4.5 years. Some reports showed that PC chemotherapy is effective for primary and recurrent GCC of the cervix 8–11 . Nasu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Some reports showed that PC chemotherapy is effective for primary and recurrent GCC of the cervix. [8][9][10][11] Nasu et al reported a case of glassy cell carcinoma treated using conventional radiation therapy and six courses of triweekly PC chemotherapy. 12 We also considered that adjuvant PC chemotherapy is effective for GCC.…”
Section: Discussionmentioning
confidence: 99%
“…Takekuma et al. 15 reported a case of bulky GCC of the uterine cervix that responded effectively to paclitaxel and carboplatin in a neoadjuvant setting. Taken together, combination chemotherapy with paclitaxel and carboplatin seem to be effective for glassy cell carcinoma of the cervix.…”
Section: Discussionmentioning
confidence: 99%
“…Пациенткам с опухолями больших размеров в качестве неоадъювантного лечения может быть проведена химиотерапия по схеме паклитаксел + карбоплатин, это лечение позволяет уменьшить размер новообразования, что, в свою очередь, дает возможность провести хирургическое лечение таких пациенток; также данная схема лечения показала свою эффективность при рецидивах GCC [21][22][23]. При местно-распространенных формах заболевания, по данным ряда авторов, эффективными оказались схемы лекарственной терапии карбоплатин + этопозид + эпирубицин и цисплатин + этопозид + митомицин C [24,25].…”
Section: оригинальные статьиunclassified